Bioabsorbable polymers in cancer therapy: latest developments. Issue 1 (December 2015) - Fonseca, Ana; Serra, Arménio; Coelho, Jorge
Abstract Cancer is a devastating disease, being responsible for 13 % of all deaths worldwide. One of the main challenges in treating cancer concerns the fact that anti-cancer drugs are not highly specific for the cancer cells and the "death" of healthy cells in the course of chemotherapy treatment is inevitable. In this sense, the use of drug delivery systems (DDS) can be seen as a powerful tool to minimize or overcome this very important issue. DDS can be designed to target specific tissues in order to mitigate side effects. Bioabsorbable polymers, due to their inherent characteristics, and because they can be synthesized in a variety of forms, are materials whose importance in the DDS for cancer therapy has risen significantly in the last years. This review intends to give an overview about the latest developments in the use of bioabsorbable polymers as DDS in cancer therapy, with special focus on nanoparticles, micelles, and implants.